Numerical simulation of coal pillar strength - Jaiswal A.; Shrivastva B.K. (My University, 2025)
The present paper describes an approach for estimation of strain-softening constitutive behaviour of coal-mass through calibration of a numerical model with field cases. A three-dimensional finite element model was used, in which the coal-mass was considered to be a Hoek-Brown strain-softening material. Dilation behaviour was considered to be a function of confinement and plastic shear strain. The numerical model was calibrated by satisfying the (1) various failed/stable cases of coal pillar of Indian coal mines and (2) post-failure behaviour of large-scale coal pillars determined by various researchers through conducting in-situ tests. The calibration of the model was done by taking various permutation and combination of strain-softening parameters. It has been concluded that the yielding of the pillars start almost at 2/3 of the peak strength. The statistical expressions for estimation of pillar strength for Indian coal mines and post-failure modulus have been developed by analyzing the results of the simulations. For Indian coal pillars having width-to-height ratio (w/h) less than five, the pillar strength was almost linearly dependent on w/h, and non-linearly dependent on uniaxial compressive strength of the coal specimen. The post-failure modulus of coal pillars was non-linearly dependent on w/h, and not significantly dependent on the uniaxial compressive strength. © 2008 Elsevier Ltd. All rights reserved.